The role of credit aggregates and asset prices in the transmission mechanism: a comparison between the euro area and the US - Sylvia Kaufmann; Maria Teresa Valderrama (European Central Bank (ECB), 2007)
We analyze the interaction between credit and asset prices in the transmission of shocks to the real economy. We estimate a Markov switching VAR for the euro area and the US, including additionally GDP, CPI and a short-term interest rate. We find evidence for two distinct states in both regions. For the euro area, we find a regime which is correlated to the business cycle and which captures periods of very low real credit growth at the end of recessions. However, during this regime credit markets and asset price markets do not impede economic recovery. In the other regime, we do find a procyclical effect of credit and asset price shocks on GDP. Shocks in both variables explain each about 20% of GDP's forecast error variance after four years. Credit shocks have a positive effect on inflation and explain about 35% of the forecast error variance, which confirms that credit aggregates contain information about the monetary stance. The effect of asset price shocks on inflation is insignificant and their share in explaining the forecast error variance negligible. For the US, regime 1 captures periods of stable GDP growth, and low and stable inflation, combined with accelerating asset prices. We find procyclical effects of credit and asset price shocks on GDP only in regime 2. Shocks in both variables explain about the same share (20%) of GDP forecast error variance, whereby the share explained by asset price shocks is about two and a half times larger than in regime 1. Shocks to credit and asset prices have no significant effect on CPI and explain each about 10% of its forecast error variance in both regimes. This is consistent with the view that monetary policy may achieve price stability without necessarily achieving financial stability.
Keywords: C11; C32; E32; E44; 330; asset prices; Asymmetry; financial system; lending; transmission mechanism; Geldpolitische Transmission; Schock; Geldpolitik; Kreditmarkt; Euro; US-Dollar; EU-Staaten; USA